Discharge of residual debt: Do private and institutional lenders differ? - Oliver Kirchkamp; Henning Prömpers (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
With the help of lab experiments we study the impact of discharging insolvent debtors of their residual debt. We investigate the impact of different participation rules and the impact of different types of lenders. We find that higher participation rates encourage risk taking behaviour of borrowers. Higher participation rates also reduce the amount of moonlighting. Most importantly, institutional lenders can suffer more from moonlighting than private lenders.
Keywords: C92; D14; D86; 330